Generator sets for the selection of key differences in the Biclique Attack - de Carvalho, G. C.; Kowada, L. A. B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2022)
Biclique cryptanalysis is the only known method faster than brute force for some block ciphers, such as the AES. The main phase of the attack is the Preparation phase in which the attacker selects the two families of key differences and chooses ways to partition the key space and the cipher. In the versions of biclique cryptanalysis used in literature, the selection of both families of key differences is done over the same set of key bits. We introduce our novel technique that involves a new concept of generator set of key differences where each key difference can be chosen from distinct sets of key bits. This also influences the way that the key space is partitioned, allowing for new possible bicliques with better time or data complexities. To demonstrate the power of this new technique, we present in this work an attack on the Serpent-256 that uses a negligible amount of data and remains close in terms of time complexity when compared to the best biclique attack applied to the cipher.